Motivating Social Influencers to Engage in Health Behavior Interventions - Smit, Crystal R.; Bevelander, Kirsten E.; de Leeuw, Rebecca N. H.; Buijzen, Moniek (Frontiers in Psychology, 2022)
Social influencers are widely known as the promotors of purchase behavior as well as for their potential to change health behaviors among individuals in their social networks. For social influencers to be successful in changing behaviors, it is essential that they convey their message in an authentic, original, credible, and persistent manner. In the context of health behavior interventions, this requires a focus on the motivation of social influencers to engage in the intervention. This perspective article describes the importance of motivating social influencers to engage in desired health behaviors themselves and to promote it within their social network. We briefly describe the current state of knowledge and our empirical experience in implementing health interventions with social influencers. Using insights from self-determination theory, we demonstrate how social influencers can be motivated optimally in health behavior interventions and, thereby, improving the success of the intervention. To illustrate these insights and guide intervention practice, we provide concrete examples of techniques that can be applied in health intervention involving social influencers. We conclude with directions for further research and intervention practice to improve the delivery of health behavior interventions.